CORRUPTION IN LAND ADMINISTRATION AND GOVERNANCE: A HURDLE TO TRANSITIONAL JUSTICE IN POST-APARTHEID SOUTH AFRICA? - Gaopalelwe Mathiba (Obiter, 2021)
The persistence of corruption in post-apartheid South Africa and the failure to control it adequately pose a significant threat to the country’s transitional justice project and transformation imperatives. This article provides a detailed account of the depth and impact of corruption in land administration and governance in South Africa. It relies on the documented evidence of corruption scandals to establish the emerging trends, scope and impact of land-related corruption. The article is premised on the notion that corruption (which has become an intrinsic political norm in South Africa) not only impedes development and exacerbates rife inequalities in land ownership and access as a result of the apartheid regime, but also strangles the aims and objectives of transitional justice, which are to alleviate those inequalities. A further premise is that land-related corruption is a direct manifestation of untrammeled political power, patronage and impunity. The article problematises the latter premise and tackles the former by attempting to understand the complex interfaces between land, human rights, corruption and women in South Africa. Women are singled out from vulnerable groups because land ownership has traditionally been, and arguably still is, a male privilege. Of concern is the scale and pace of corruption, which boosts this anomaly, allowing it to thrive exponentially in post-apartheid South Africa. The article also presents a brief overview of operational and institutional challenges facing various initiatives aimed at combatting corruption generally. It concludes by proposing some realistic options to consider for the way forward.